A microfluidic organotypic device for culture of mammalian intestines ex vivo. Issue 3 (17th December 2019) - Richardson, Alec; Schwerdtfeger, Luke A.; Eaton, Diana; Mclean, Ian; Henry, Charles S.; Tobet, Stuart A.
Abstract : A microfluidic organotypic device that maintains mouse colon explants for up to 72 h in a physiologically relevant environment is reported. The device is easy to assemble and maintains physiologically accurate oxygen concentrations across the tissue. Abstract : The physiological characteristics of the gastrointestinal (GI) tract are diverse and include rapid rates of epithelial turnover, complex nervous and immune systems, a thick mucus layer, and a large microbial population. Most GI models in vitro rely upon cell lines or organoids and consequently lack the diversity of cells and microorganisms present in vivo . In vivo studies retain function and cellular diversity but are more difficult to control. Microfluidic tissue-on-a-chip devices provide powerful alternatives for modeling physiological systems. Such devices show promise for use in GI research; however, most models use non-physiologic culture environments with higher than in vivo oxygen levels and insufficient gut microbiota. Our goal is to create a bridge between in vitro and in vivo using microfluidic devices by incorporating ex vivo tissue explants in physiologically relevant environments. Here, we report a microfluidic organotypic device (MOD) that enables media flow with differential oxygen concentrations across luminal and muscular surfaces of gut tissue ex vivo . Tissue was shown to be viable for 72 h and lowering oxygen concentration to a more physiologic level impacted bacterial populations.